Perancangan Sistem Informasi Jadwal Dokter Menggunakan Framework Codeigniter - Sallaby, Achmad Fikri; Kanedi, Indra (UNIVED Press, 2020)
Hospitals and Community Health Centers or clinics are institutions that operate in the field of public health services. It is very important for hospitals, health centers and clinics to display doctor schedules. This is done so that patients know the Doctor's Practice Schedule at that time more accurately. An information system is a collection of unified data that is properly and correctly informed and the information conveyed can also be received well. The system development method used is the waterfall model. Design analysis includes Use Case Diagrams, Activity Diagrams, Class Diagrams, and Sequence Diagrams. Implementation uses tools such as the CodeIgniter Framework as interface design and MySQL as database processing.Keywords: Hospital, Community Health Center, Clinic, Information System, Waterfall, Use Case Diagram, Activity Diagram, Class Diagram, Sequence Diagram Framework CodeIgniter and MySQL.